Synthesis and antitumor activity of 2‐isocamphanyl thiosemicarbazone derivatives via ROS‐enhanced mitochondrial damage. (5th June 2019) - Wang, Yunyun; Wang, Zhonglong; Kuang, Hongbo; Zhang, Yan; Gu, Wen; Zhu, Yongqiang; Wang, Shifa
Abstract: A series of novel 2‐isocamphanyl thiosemicarbazone derivatives were synthesized and characterized by 1 H NMR, 13 C NMR, and HRMS. In in vitro anticancer activity, most derivatives showed considerable cytotoxic activity against four cancer cell lines (RPMI‐8226, A549, MDA‐MB‐231, and HepG2 cancer cells) and showed low toxicity against human gastric mucosal cells (GES‐1). Among them, compound4h exhibited excellent antitumor activity against the tested cancer cells with IC50 values of 0.4, 1.1, 1.6, and 1.7 μM for MDA‐MB‐231, RPMI‐8226, A549, and HepG2, respectively. Further, mechanism studies indicated that compound4h induced apoptosis in MDA‐MB‐231 cells through enhancing reactive oxygen species levels, inducing mitochondrial membrane potential decrease, and influencing the expression of Bax, Bcl‐2, caspase‐3, and caspase‐9. Abstract : A series of novel 2‐isocamphanyl thiosemicarbazone derivatives were synthesized and evaluated for their antitumor activities in vitro. Among them, compound4h showed significant antitumor activities. Further study demonstrated that ROS‐enhanced mitochondria damage relates to the antitumor mechanism of compound4h .